Simple hardware-oriented algorithms for cellular mobiles positioning - Najiminaini, M.; Doukhnitch, E.; Salamah, M. (IEEE, 2007)
locating a mobile station position is one of the most significant features of cellular mobile phones in wireless communications. All location determination algorithms are based on trigonometric calculations which are usually implemented in software. In this paper, we propose two new hardware oriented algorithms that use just simple add, shift and subtract operations in finding the location of a mobile station. The first algorithm uses fixed rotations to locate a mobile station position. The second algorithm is a dynamic version of the first one. It uses dynamic rotations to find the location of the mobile. Via simulation, the computational cost and error (in meter) for the traditional algorithm, the fixed rotation hardware-oriented algorithm, and the dynamic version are compared.
IEEE International Conference on Pervasive Services -- JUL 15-20, 2007 -- Istanbul, TURKEY
Keywords: vector rotation; local determination; hardware oriented algorithm